Independent predictors of major adverse cardiovascular events in emergency department patients who are hospitalised with a suspected infection: a retrospective cohort study. Issue 1 (27th January 2016) - de Groot, Bas; van den Berg, Stefanie; Kessler, Joanne; Ansems, Annemieke; Rijpsma, Douwe
Abstract : Objective: Emergency department (ED) patients hospitalised with a suspected infection have an increased risk for major adverse cardiovascular events (MACE). This study aims to identify independent predictors of MACE after hospital admission which could be used for identification of high-risk patients who may benefit from preventive strategies. Setting: Dutch tertiary care centre and urban hospital. Participants: Consecutive, hospitalised, ED patients with a suspected infection. Design: This was a secondary analysis using an existing database in which consecutive, hospitalised, ED patients with a suspected infection were prospectively enrolled. Potential independent predictors, including illness severity, as assessed by the Predisposition, Infection, Response, Organ failure (PIRO) score, and classic cardiac risk factors were analysed by multivariable binary logistic regression. Prognostic and discriminative performance of the model was quantified by the Hosmer-Lemeshow test and receiver operator characteristics with area under the curve (AUC) analyses, respectively. Maximum sensitivity and specificity for identification of MACE were calculated. Primary outcome: MACE within 90 days after hospital admission. Results: 36 (2.1%) of the 1728 included patients developed MACE <90 days after ED presentation. Independent predictors of MACE were the RO components of the PIRO score, reflecting acute organ failure, with a corrected OR (OR (95% CI) 1.1 (1.0 to 1.3) per point increase), presence of atrial fibrillation/flutter; OR 3.9 (2.0 to 7.7) and >2 classic cardiovascular risk factors; 2.2 (1.1 to 4.3). The AUC was 0.773, and the goodness-of-fit test had a p value of 0.714. These predictors identified MACE with 75% sensitivity and 70% specificity. Conclusions: Besides the classical cardiovascular risk factors, atrial fibrillation and signs of acute organ failure were independent risk factors of MACE in ED patients hospitalised with a suspected infection. Future studies should investigate whether preventive measures like antiplatelet therapy should be initialised in hospitalised ED patients with suspected infection and high risk for MACE.